2019
DOI: 10.1101/703793
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Evolutionary History of Common Genetic Variants Influencing Human Cortical Surface Area

Abstract: Structural brain changes along the lineage that led to modern Homo sapiens have contributed to our unique cognitive and social abilities. However, the evolutionarily relevant molecular variants impacting key aspects of neuroanatomy are largely unknown. Here, we integrate evolutionary annotations of the genome at diverse timescales with common variant associations from large-scale neuroimaging genetic screens in living humans, to reveal how selective pressures have shaped neocortical surface area. We show that … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…In addition, we are aware that variants enter the genome at one stage and are likely selected for at a (much) later stage [29,30]. As such our study differs from the chronological atlas of natural selection in our species presented in [31] (as well as from other studies focusing on more recent periods of our evolutionary history, such as [32]). This may explain some important discrepancies between the overall temporal profile of genes highlighted in [31] and the distribution of HF variants for these genes in our data ( Figure S7).…”
Section: Variant Subset Distributionsmentioning
confidence: 83%
“…In addition, we are aware that variants enter the genome at one stage and are likely selected for at a (much) later stage [29,30]. As such our study differs from the chronological atlas of natural selection in our species presented in [31] (as well as from other studies focusing on more recent periods of our evolutionary history, such as [32]). This may explain some important discrepancies between the overall temporal profile of genes highlighted in [31] and the distribution of HF variants for these genes in our data ( Figure S7).…”
Section: Variant Subset Distributionsmentioning
confidence: 83%
“…These discoveries resulted in an annotated atlas of common genetic variants that contribute to shaping the human cerebral cortex. Of particular interest, we found that genetic loci affecting brain morphology show enrichment for developmentally regulated genes 13 and human-specific regulatory elements 26,27 . Ongoing efforts are beginning to map these genetic effects at a finer-grained spatial resolution using shape analysis, surface-and voxel-based analyses [28][29][30][31] .…”
Section: Uncovering the Genetic Basis Of Brain Morphometric Variationmentioning
confidence: 99%
“…Multimodal association cortices including frontal, temporal, and parietal areas are evolutionarily modern areas and present a higher cortical surface expansion in humans with respect to macaque [79]. Interestingly, high expanding regions are less mature at term gestation functionally and structurally allowing shaping by environmental factors [76,80,81] and mature slowly in developmental stages [76]. Regional differences in white matter maturation in later childhood development supports variability in structural connectome [82,83,84].…”
Section: Structural and Functional Interindividual Variability Is Heterogenous Across Cortical Surfacementioning
confidence: 87%